2011
DOI: 10.1016/j.bandc.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mothers’ past infant-holding preferences on their adult children’s face processing lateralisation

Abstract: Face processing development is negatively affected when infants have not been exposed to faces for some time because of congenital cataract blocking all vision (Le Grand, Mondloch, Maurer, & Brent, 2001). It is not clear, however, whether more subtle differences in face exposure may also have an influence. The present study looked at the effect of the mother's preferred side of holding an infant, on her adult child's face processing lateralisation. Adults with a mother who had a left-arm preference for holding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…The idea that the frequent interaction with right-handed individuals might promote leftward biases is consistent not only with both the experience-expectant and the experience-dependent view of brain development (Greenough et al, 1987), but also with previous studies showing that experience can affect the lateralization of face processing (e.g., infant holding biases; Vervloed et al, 2011; reading habits; Vaid and Singh, 1989; Sakhuja et al, 1996; Heath et al, 2005; Megreya and Havard, 2011). However, the fact that eye tracking studies reveal that a left visual field bias during face observation emerges within 9–11 months (Wheeler, 2010; Liu et al, 2011; Dundas et al, 2012b) and the fact that the leftward bias becomes more specific for upright human faces with increasing age (Guo et al, 2009) indicate that reading habits cannot account for the emergence of the bias.…”
Section: Developmental Trend In the Left Face Bias: Is There A Role Fsupporting
confidence: 84%
See 1 more Smart Citation
“…The idea that the frequent interaction with right-handed individuals might promote leftward biases is consistent not only with both the experience-expectant and the experience-dependent view of brain development (Greenough et al, 1987), but also with previous studies showing that experience can affect the lateralization of face processing (e.g., infant holding biases; Vervloed et al, 2011; reading habits; Vaid and Singh, 1989; Sakhuja et al, 1996; Heath et al, 2005; Megreya and Havard, 2011). However, the fact that eye tracking studies reveal that a left visual field bias during face observation emerges within 9–11 months (Wheeler, 2010; Liu et al, 2011; Dundas et al, 2012b) and the fact that the leftward bias becomes more specific for upright human faces with increasing age (Guo et al, 2009) indicate that reading habits cannot account for the emergence of the bias.…”
Section: Developmental Trend In the Left Face Bias: Is There A Role Fsupporting
confidence: 84%
“…Another factor reported to affect the leftward bias for faces is maternal preferred cradling side: adults whose mother had an atypical right-side preference for holding infants show a reduced left-bias for chimeric faces compared to adults whose mother had the typical left-side preference (Vervloed et al, 2011). Interestingly, the maternal cradling side is also related to children’s handedness, right-cradled infants having slightly higher odds of being left-handed at 19 months of age (Scola and Vauclair, 2010).…”
Section: Developmental Trend In the Left Face Bias: Is There A Role Fmentioning
confidence: 99%
“…In other words, attachment is capable of influencing human life "from the cradle to the grave" (see Bowlby, 1969Bowlby, /1982 and of orienting all human social behaviors. Similarly to positive and negative attachment patterns (e.g., Benoit & Parker, 1994), cradling-side preferences can be transmitted from one generation to the other, as shown by Manning and Denman (1994), which further corroborates the view that optimal and secure attachment patterns shown by left-cradling mothers seem to reflect the optimal emotional information they can provide to their children during early childhood, which in turn can also facilitate the development of typical brain asymmetries as measured in adulthood (e.g., see Hendriks, van Rijswijk, & Omtzigt, 2011;Vervloed, Hendriks, & van den Eijnde, 2011). It is also noteworthy that the proportion of left cradlers did not differ between participants showing optimal and nonoptimal attachment to their fathers.…”
Section: Doll Position Left Midline Right Left Versus Rightsupporting
confidence: 72%
“…gaze, facial expression) to maintain a direct route to the right hemisphere (for a review, see Scola & Vauclair, 2010b). This interpretation gains support from a study that indicated that children who were held with a left arm preference demonstrated a typical left visual field (right hemisphere) bias for faces on chimeric face tests, whereas individuals who were held with a right-arm lacked a visual field bias (Vervloed, Hendriks, & van den Eijnde, 2011). The ramification of hemispheric bilateralization for social-emotional processing has yet to be explored within the scope of cognitive development.…”
Section: Introductionmentioning
confidence: 99%